(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
Peristaltic motion of an incompressible micropolar fluid in a two-dimensional channel with wall effects is studied. Assuming that the wave length of the peristaltic wave is large in comparison to the mean half width of the channel, a perturbation method of solution is obtained in terms of wall slope parameter, under dynamic boundary conditions. Closed form expressions are derived for the stream function and average velocity and the effects of pertinent parameters on these flow variables have been studied. It has been observed that the time average velocity increases numerically with micropolar parameter. Further, the time average velocity also increases with stiffness in the wall.